Kisspeptin/G protein-coupled receptor-54 system as an essential gatekeeper of pubertal development - Young-Jun Rhie (Korean Society of Pediatric Endocrinology, 2013)
Puberty is the end-point of a complex series of developmental events, defined by the dynamic interaction between genetic factors and environmental cues, ultimately leading to the attainment of reproductive capacity. Kisspeptins, products of the KISS1 gene, were originally identified as metastasis suppressor peptides with the ability to bind G protein-coupled receptors (GPR54). In 2003, loss-of-function mutations of the GPR54 gene were found in patients with hypogonadotropic hypogonadism. This finding triggered study of the role of the kisspeptin/GPR54 system as an essential gatekeeper of control of reproduction and pubertal development. Kisspeptins are very potent elicitors of gonadotropin secretion, primarily through stimulation of gonadotropin-releasing hormone release. KISS1 also functions as an essential integrator for peripheral inputs, including gonadal steroids and nutritional signals, and for controlling GnRH and gonadotropin secretion. Whether the kisspeptin/GPR54 system is the trigger for puberty onset and/or it operates as integrator and effector of up-stream regulatory factors warrants further investigation.